Perspektif dan Pendekatan Teori Manajemen yang telah berkembang Sepanjang Sejarah - Maulana, Gilang; Anwar US, Kasful (Transpublika Publisher, 2021)
Abstract: Theory is a thing that is seen as monotonous and hinders fieldwork for people who are used to the field, but the real purpose of theory is to determine the professional nature of workers, just as management theory is needed to manage worker activities in order to get work agreements. which is good and does not burden one side, both from the workers and the company. This journal contains the stages of development of management theory in the world, compiled based on references that are owned even though they are limited Keywords: Management, Workers, Professionalism